Specific Professional-Psychological Competencies Of The Managerial Personality And Thepsychological Portrait Of A Competent Leader - Nazarov Azamat Sottarovich (Genius Journals, 2025)
This article analyzes the socio-psychological and professional competencies of a leader. The article analyzes the psychological components of a leader and cultured leader.
Keywords: management decisions; conscious choice; determinism